Population Structure and Regeneration of Mallotus philippensis in Sal Forests of Kumaun Himalaya - Adhikari, Bhawna; Lodhiyal, Neelu; Kapkoti, Bhawana; Lodhiyal, L.S.; Rawat, P.S. (Indian Forester, 2019)
Present study deals with the population structure and regeneration of Mallotus philippensis in different forests i.e. sal dominant, sal mixed and sal open canopy forests of Kumaun Himalaya of Uttarakhand. The density of seedlings, saplings and trees ranged from 920 -1200, 13-160 and 7-127 ind.ha'', respectively. As far as regeneration of Mallotus philippensis Is concerned. It was found good regeneration in sal mixed forest and sal open canopy forest, whereas the sal dominant forest had shown fair regeneration. On the basis of study, it is concluded that the forest site which has sufficient nutrient, moisture and proper availability of sunlight, the regeneration of Mallotus philippensis was good.